Utilization of Quizizz as a Learning Medium for Elementary Teachers in Cisauk District - Sri Hapsari Wijayanti; Heru Prasadja; Anthony Devonico Putera Pasau; Aurelius Andreas (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Digital competence is a competency that must be possessed by teachers in the digital era. However, this skill turned out to be a big obstacle during the covid-19 pandemic. Many teachers have not been able to take advantage of technology, so in learning, there are still those who rely on WhatsApp as a learning tool. Elementary school teachers in Cisauk District who are members of PGRI (Persatuan Guru Republik Indonesia) reported that student learning outcomes during the covid-19 pandemic were no better than before and they realized that students were less motivated. The purpose of this community service activity is to improve the knowledge and ability of teachers in Cisauk District in using Quizizz. This activity was held in virtual training for 46 teachers and school principals. The methods used are discussion, demonstration, assignment, monitoring, mentoring, and evaluation. The teacher is given the task of making a Quizizz and testing it for their students in class. Teachers are also accompanied and guided in completing assignments. From the results of the training, teachers showed an increase in knowledge and skills using Quizizz. Quizizz also has a positive response from students.